Rescue of transforming Epstein-Barr virus (EBV) from EBV-genome-positive epithelial hybrid cells transfected with subgenomic fragments of EBV DNA - Stoerker, Jay (1983)
Transfection experiments using subgenomic fragments of the B95-8 strain of Epstein-Barr virus (EBV) DNA and EBV genome (HR-1)-positive epithelial/Burkitt hybrid cells (D98/HR-1) were carried out to determine whether an interaction between the transfecting virus fragment(s) and the endogenous HR-1 EBV genome could take place. Expression of EBV-specific antigens, including early antigen and virus capsid antigen, was examined in transfected cells by immunofluorescence. Attempts were also made to recover biologically active EBV from the D98/HR-1 cells after transfection with cloned fragments of B95-8 DNA. We found that D98/HR-1 cells transfected with the BamHI H or H, F, and X fragments were positive for early antigen 3 days after transfection. Spent media from transfected D98/HR-1 cells maintained for 20-30 days in culture were pooled, filtered, concentrated, and used as a potential source of virus to inoculate human umbilical cord blood lymphocytes. No evidence of transformation was observed with such preparations. However, if spent medium from D98/HR-1 cell cultures was first treated with iododeoxyuridine (to induce EBV DNA synthesis and replicative cycle) and then transfected with the BamHI H, F, and X fragments of B95-8 DNA and used to infect cord blood lymphocytes, transformation was obtained. A lymphoblastoid cell line derived in this manner, designated HI-HFX, is an EBV nuclear antigen-positive nonproducer cell line. Similar results were obtained with preparations from iododeoxyuridine-treated D98/HR-1 cells transfected with the EB 26-36 fragment of B95-8 DNA cloned in a Charon 4A vector. The EB 26-36 fragment contains the BamHI H, F, and X regions.